2021
DOI: 10.1159/000512955
|View full text |Cite
|
Sign up to set email alerts
|

Clear-Cell Adenocarcinoma of the Gallbladder with Alpha-Fetoprotein Production: A Case Report and Review of the Literature

Abstract: Gallbladder tumors are the fifth most common cancers of the gastrointestinal tract with poor prognosis and low survival. The most common type is adenocarcinoma of which the clear cell type is an unusual histologic variant with alpha-fetoprotein (AFP)-producing gallbladder carcinoma, reported extremely rarely, which makes the index case an uncommon entity. AFP secretion by gallbladder carcinomas may occur given the similar embryological origin of liver and gallbladder. Herein we report a case of an incidental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Bittinger et al initially determined that if CK7 and CEA reactivity is detectable, then the lesion is either primary of the gallbladder or metastatic of a lung mass, excluding clear cell carcinomas of other tissues [ 20 ]. In later years, Zhang et al and Dixit et al observed that CEA and CK7 were strongly stained in the gallbladder but were negative in nearly all other clear cell carcinomas, including the renal one [ 5 , 17 ]. More recently, Sarangi et al added that CCG is also positive for CK19, which is not seen in renal clear cell carcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bittinger et al initially determined that if CK7 and CEA reactivity is detectable, then the lesion is either primary of the gallbladder or metastatic of a lung mass, excluding clear cell carcinomas of other tissues [ 20 ]. In later years, Zhang et al and Dixit et al observed that CEA and CK7 were strongly stained in the gallbladder but were negative in nearly all other clear cell carcinomas, including the renal one [ 5 , 17 ]. More recently, Sarangi et al added that CCG is also positive for CK19, which is not seen in renal clear cell carcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was observed by Vardaman and Albores-Saavedra and they suggested that such neoplasms should be considered primary until proven otherwise [25]. During the following years, that CEA and CK7 were strongly stained in the gallbladder but were negative in nearly all other clear cell carcinomas, including the renal one [5,17]. More recently, Sarangi et al added that CCG is also positive for CK19, which is not seen in renal clear cell carcinoma [19].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Only a few cases of AFP-producing gallbladder carcinomas have been reported in the literature, and most of these cases have exhibited papillary or hepatoid morphologies and poor prognosis [14] . Primary AFP-producing gallbladder carcinomas reported in the recent English literature consist of four histologic types: undifferentiated carcinoma, poorly differentiated carcinoma, clear cell carcinoma, and hepatoid carcinoma ( Table 1 ) [15] , [16] , [17] , [18] . In our patient, histopathological studies revealed poorly differentiated adenocarcinoma with signet ring cells, and immunohistochemical studies showed AFP production.…”
Section: Discussionmentioning
confidence: 99%